Self-Efficacy and Cognitive on Academic Achievement of Klabat University Nursing Student - Anderson, Griffin Mark Owen; Anderson, Elisa (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Self-efficacy is belief in one's ability in lectures, while cognitive is reasoning and can change the way students learn. Students with bad ways of studying can have an impact on their academic achievement. This study aims to determine the correlation of self-efficacy and cognitive on academic achievement of nursing students at Klabat University. This research uses a cross-sectional method, involving 334 respondents through consecutive sampling techniques. The results of this study prove that most of the nursing students at the University of Klabat, 151 (45.2%) had self-efficacy in the moderate category, 227 (86%) students got cognitive in the poor category, and 147 (44%) got academic achievement A category. There is a significant correlation between self-efficacy on student academic achievement (p=0.010) and cognitive relationship on student academic achievement (p=0.000). Students need to improve self-efficacy by increasing learning, so they can have more confidence in their own abilities and develop cognitive skills by studying cognitive tests such as problem-solving questions so that academic achievement in lectures can be maintained or increased. It is recommended that further researchers who will conduct research with the title of self-efficacy and cognitive on academic achievement can find out other factors that can affect academic achievements such as living environment, religion or belief, association, teaching techniques from educators, and duration of learning while on campus or at home. Keywords : nursing students, self-efficacy, cognitive, academic achievement